2014
DOI: 10.1097/jom.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Return on Investment From a Health Risk Management Program Offered to Small Colorado-Based Employers

Abstract: Objective To determine whether changes in health risks for workers in small businesses can produce medical and productivity cost savings. Methods A 1-year pre- and posttest study tracked changes in 10 modifiable health risks for 2458 workers at 121 Colorado businesses that participated in a comprehensive worksite health promotion program. Risk reductions were entered into a return-on-investment (ROI) simulation model. Results Reductions were recorded in 10 risk factors examined, including obesity (−2.0%), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 25 publications
0
43
0
2
Order By: Relevance
“…As in most HEE (66), our data showed that indirect costs (productivity) were the main cost-drivers. For example, in the study by Goetzel et al (50), the ROI was -42% excluding indirect costs but 103% including indirect costs. A systematic review found that PA was related to increased psychosocial health in employees (27) and there is also evidence that such health outcomes reduce presenteeism (67).…”
Section: Health Economic Evaluationsmentioning
confidence: 97%
“…As in most HEE (66), our data showed that indirect costs (productivity) were the main cost-drivers. For example, in the study by Goetzel et al (50), the ROI was -42% excluding indirect costs but 103% including indirect costs. A systematic review found that PA was related to increased psychosocial health in employees (27) and there is also evidence that such health outcomes reduce presenteeism (67).…”
Section: Health Economic Evaluationsmentioning
confidence: 97%
“…The remaining 4 studies (4%) all used ad hoc approaches that (41, 45-48, 51, 56-58, 60, 62, 64, 66, 68, 70, 72-75, 79, 81, 83, 84, 87-90, 92, 93, 95, 97, 98, 100-102, 105, 107-110, 113, 117-125) North-America 34 (39, 40, 43, 44, 50, 52-55, 59, 61, 63, 65, 69, 71, 76, 80, 82, 85, 86, 91, 94, 96, 99, 103, 106, 111, 112, 114-116, 126- (39, 41, 42, 44, 45,49,50,(52)(53)(54)(55)59,60,67,68,70,71,76,77,82,87,95,115, 128) Inferred: 19 (40, 43, 46,57,61,63,65,80,86,91,92,94,96,103,111,116,(125)(126)(127)56,62,64,66,69,72,73,75,78,79,81,(83)(84)(85)…”
Section: Productivity Estimation Methodsmentioning
confidence: 99%
“…Measure for reduced productivity at work/ while working 31 (39, 41-44, 56, 60-65, 69, 70, 72, 77, 82, 87, 89, 94, 95, 98, 103, 104, 114, 115, 118, 119, 123, 124, 128) Source presenteeism Employee survey 18 (41, 44,56,62,64,69,72,82,87,89,94,95,98,104,115,118,119, 123) Simulated / assumptions 7 (39, 43, 44,103,114,124, 128) Previous studies 6 (42,60,61,63,65,70) Firm data 1 (115) Employer survey 1 (77) Survey/instrument presenteeism 56,62,69,82,94,95,118,119,123) Days (unspecified) 49 (39, 40, 42, 46,49,(51)(52)(53)(54)58,60,62,64,66,71,72,74,75,(77)(78)…”
Section: Presenteeismmentioning
confidence: 99%
See 1 more Smart Citation
“…This partnership resulted in several peer reviewed publications outlining the need for businesses to address the health, safety, and productivity of employees. 4,[21][22][23][24][25] However, the partners were aware of the need to disseminate these findings to businesses in a way that resonated with them to ultimately help facilitate action to enhance their employee's health and safety at work.…”
Section: Introductionmentioning
confidence: 99%